Use of a cooling pack to reduce subcutaneous vaccine injection pain in children aged 3–6 years: A single-blind, randomized, parallel-group multicenter study - Ikuo Okafuji; Ryuta Washio; Takao Okafuji; Yu Tanaka; Tatsuo Kagimura (PLoS ONE, 2025)
Background There are many evidence-based treatments available for pain-relief during subcutaneous vaccine injection in children. However, these methods are commonly labor-intensive and not routinely applied in clinical settings. Objectives To evaluate the safety and pain-relieving effect of local cooling during subcutaneous vaccine injection in young children. Method This single-blind, randomized, parallel-group multicenter study was conducted at two pediatric clinics in Hyogo Prefecture, which included preschool children aged 3–6 years scheduled for vaccination against Japanese encephalitis or influenza virus. Participants were randomly assigned to either the cooled group (local cooling applied using a cooling pack before vaccination) or the non-cooled group (provided with a room temperature cooling pack). Randomization was performed using a computer-generated block method. The primary endpoint was infant pain, measured using the FLACC scale (Facial expression, Leg movement, Activity, Crying, Consolability), rated by a third-party reviewing videos of the vaccination process. Results A total of 60 children were randomized into the cooling (n = 30) and non-cooling (n = 30) groups, with all participants completing the study. Fifty-four participants received the Japanese encephalitis vaccine, and six received the influenza vaccine. Demographic data, including age, sex, and vaccine type, did not differ significantly between the two groups. The median FLACC score in the cooled group was significantly lower (1 [IQR 0–1.25]) compared to the non-cooled group (2.5 [IQR 1–6]) (P = 0.011). No adverse effects related to cooling were observed. Conclusion Local cooling during subcutaneous vaccine administration is a safe and effective method to reduce pain in children aged 3-6 years. This method can be easily implemented in routine vaccinations to improve patient comfort. Trial registration Japan Registry of Clinical Trials, jRCTs052200149, Mar 09, 2021, https://jrct.niph.go.jp/en-latest-detail/jRCTs052200149.